Numerical conformal mapping onto the entire complex plane bounded with finite straight slit and logarithmic spiral slits - Yunus A.A.M.; Yunus A.; Nasser M.M.S. (Institute of Physics Publishing, 2024)
This paper presents a fast boundary integral equation method with for computing conformal mappings of multiply connected regions. We consider the canonical region consists of the entire complex plane bounded by a finite straight slit on the line Im ? = 0 and finite logarithmic spiral slits. Some numerical examples are given to show the effectiveness of the proposed method.